"Dealing with the Legally Accountable According to the Opposite of Their Illegitimate Purpose" - Mohamed, Al-Qayati , Khalid ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2015)
This study addresses the legal maxim of treating the accountable individual according to the opposite of their corrupt intent for several reasons: First, the role of this maxim in activating the objectives of Islamic law (Maqāṣid al-Sharīʿah), as these objectives remain theoretical unless they are considered in light of the intentions of those subject to the law. Second, despite the significance of this maxim, it has not, to the best of the author's knowledge, been the subject of an independent study. Most of the existing literature mentions it only briefly within broader discussions of legal maxims, without focusing on its theoretical foundations, detailed applications, or its relationship with the objectives of Islamic law—an endeavor this study aims to undertake. Third, to encourage Muslims to pursue lawful means in order to achieve their interests, and to dissuade them from adopting unlawful means that ultimately lead to results contrary to their intentions